Changes in thermotolerance and Hsp70 expression with domestication in Drosophila melanogaster. - Krebs, R.A.; Roberts, S.P.; Bettencourt, B.R.; Feder, M.E. (Journal of Evolutionary Biology, 2001)
To examine how the duration of laboratory domestication may affect Drosophila stocks used in studies of thermotolerance, we measured expression of the inducible heat-shock protein Hsp70 and survival after heat shock in D. melanogaster strains recently collected from nature and maintained in laboratory culture for up to 50 or more generations. After an initial increase in both Hsp70 expression and thermotolerance immediately after transfer to laboratory medium, both traits remained fairly constant over time and variation among strains persisted through laboratory domestication. Furthermore, variation in heat tolerance and Hsp70 expression did not correlate with the length of time populations evolved in the laboratory. Therefore, while environmental variation likely contributed most to early shifts in strain tolerance and Hsp70 expression, other population parameters, for example genetic drift, inbreeding, and selection likely affected these traits little. As long as populations are maintained with large numbers of individuals, the culture of insects in the laboratory may have little effect on the tolerance of different strains to thermal stress.